Independent resolving sets in graphs - B. Suganya; S. Arumugam (AKCE International Journal of Graphs and Combinatorics, 2021)
Let be a connected graph. Let be a subset of V with an order imposed on W. The k-vector is called the resolving vector of v with respect to W. The set W is called a resolving set if for any two distinct vertices In this paper we investigate the existence of independent resolving sets in Cartesian product and corona of graphs.